CO2 reforming of CH4 over Ni/SBA-15: Influence of Ni-loading methods - H. D., Setiabudi; N. S. A., Razak; F. R. M., Suhaimi; F. N., Pauzi (Penerbit UTM Press, Universiti Teknologi Malaysia, 2016)
A series of Ni/SBA-15 catalysts were prepared with three different methods which are impregnation (IM), ion exchange (IE) and physical mixing (PM) for CO2 reforming of CH4. The XRD, BET, FTIR and TGA analyses showed that the quantity of Ni-support interaction (Ni-O-Si) by substitution of the OH with Ni species followed the order of Ni/SBA-15(IE) > Ni/SBA-15(IM) > Ni/SBA-15(PM), while the size of Ni particles and blockage of the pores increased with the order of Ni/SBA-15(IE) < Ni/SBA-15(IM) < Ni/SBA-15(PM). At temperature studied, the activity of catalysts followed the order of Ni/SBA-15(IE) â‰ˆ Ni/SBA-15(IM) > Ni/SBA-15(PM), while the stability of catalysts followed the order of Ni/SBA-15(IE) > Ni/SBA-15(IM) > Ni/SBA-15(PM). The excellent performance of Ni/SBA-15(IE) was related with the higher formation of Ni-support interaction, which altered the properties of catalyst towards an excellent catalytic performance. Meanwhile, the lowest activity of Ni/SBA-15(PM) was related with the higher agglomeration of Ni particles that were decorating on the surface part of SBA-15 arose from the weaker Ni-support interaction. This study provides new perspectives on the Ni-based catalyst, particularly on the influence of Ni-loading methods on the properties and catalytic performance of Ni/SBA-15 towards CO2 reforming of CH4.